Will nanomedicine become a good solution for the cardiotoxicity of chemotherapy drugs? - Jiang, Yichuan; Jiang, Yueyao; Li, Min; Yu, Qian (Frontiers in Pharmacology, 2023)
Cancer is one of the leading causes of death worldwide, and with the continuous development of life sciences and pharmaceutical technology, more and more antitumor drugs are being used in clinics to benefit cancer patients. However, the incidence of chemotherapy-induced cardiotoxicity has been continuously increasing, threatening patients’ long-term survival. Cardio-oncology has become a research hot spot, and the combination of nanotechnology and biomedicine has brought about an unprecedented technological revolution. Nanomaterials have the potential to maximize the efficacy and reduce the side effects of chemotherapeutic drugs when used as their carriers, and several nano-formulations of frequently used chemotherapeutic drugs have already been approved for marketing. In this review, we summarize chemotherapeutic drugs that are highly associated with cardiotoxicity and evaluate the role of nano-delivery systems in reducing cardiotoxicity based on studies of their marketed or R&D nano-formulations. Some of the marketed chemotherapy drugs are combined with nano-delivery systems that can effectively deliver chemotherapy drugs to tumors and cannot easily penetrate the endothelial barrier of the heart, thus decreasing their distribution in the heart and reducing the cardiotoxicity to some extent. However, many chemotherapy nanomedicines that are marketed or in R&D have not received enough attention in determining their cardiotoxicity. In general, nanomedicine is an effective method to reduce the cardiotoxicity of traditional chemotherapy drugs. However, cardiovascular complications in cancer treatment are very complex diseases, requiring the application of multiple measures to achieve effective management and prevention.